Open mesh and laparoscopic total extraperitoneal inguinal hernia repair under spinal and general anesthesia - Sunamak O; Donmez T; Yildirim D; Hut A; Erdem VM; Erdem DA; Ozata IH; Cakir M; Uzman S (Therapeutics and Clinical Risk Management, 2018)
Oguzhan Sunamak,1 Turgut Donmez,2 Dogan Yildirim,3 Adnan Hut,3 Vuslat Muslu Erdem,4 Duygu Ayfer Erdem,4 Ibrahim Halil Ozata,2 Mikail Cakir,3 Sinan Uzman5 1Department of General Surgery, Haydarpasa Numune Training and Research Hospital, Istanbul, Turkey; 2Department of General Surgery, Lutfiye Nuri Burat State Hospital, Istanbul, Turkey; 3Department of General Surgery, Haseki Training and Research Hospital, Istanbul, Turkey; 4Department of Anesthesiology, Lutfiye Nuri Burat State Hospital, Istanbul, Turkey; 5Department of Anesthesiology, Haseki Training and Research Hospital, Istanbul, Turkey Introduction: Mesh placement is the main standard in repair of inguinal hernia, and laparoscopic repair is the standard of care via spinal, epidural, or combined anesthesia. Here, we compared open and laparoscopic total extraperitoneal (TEP) repairs under general (GA) and spinal anesthesia (SA).Methods: Inguinal hernia patients (n=440) were analyzed retrospectively. There were four groups: Group 1 was TEP under GA (TEP-GA) (n=111); Group 2 was open mesh repair (OM) under SA (n=116) (OM-SA); Group 3 was open mesh repair under GA (n=117) (OM-GA); Group four was TEP under SA (n=96) (TEP-SA). The age, body mass index, duration of operation, hospital stay, postoperative Visual Analog Scale scores, recurrence, postoperative pain, urinary retention, headache, and patient satisfaction were all recorded.Results: There was no significant difference in terms of hypotension, vomiting, seroma and scrotal edema, recurrence, and wound infection incidence between the groups. However, the operation duration, hospital stay period, headache, urinary retention, postoperative Visual Analog Scale scores, chronic pain, and patient satisfaction showed significant differences between groups.Conclusion: Laparoscopic TEP hernia repair is a safe and effective method along with its advantages of shorter hospital stay, less recurrence, less postoperative pain, higher patient satisfaction, and similar postoperative complication rates. SA has the disadvantage of higher incidence of headache and urinary retention compared to GA. Keywords: herniorrhaphy, laparoscopy, general anesthesia, spinal anesthesia